The Promyelocytic Leukemia Zinc Finger Protein: Two Decades of Molecular Oncology - Suliman, Bandar A.; Xu, Dakang; Williams, Bryan R. (Frontiers in Oncology, 2012)
The promyelocytic leukemia zinc finger protein (PLZF), also known as Zbtb16 or Zfp145, was first identified in a patient with acute promyelocytic leukemia, where a reciprocal chromosomal translocation t(11;17)(q23;q21) resulted in a fusion with the RARA gene encoding retinoic acid receptor alpha. The wild-type Zbtb16 gene encodes a transcription factor that belongs to the POK (POZ and Krüppel) family of transcriptional repressors. In addition to nine Krüppel-type sequence-specific zinc fingers, which make it a member of the Krüppel-like zinc finger protein family, the PLZF protein contains an N-terminal BTB/POZ domain and RD2 domain. PLZF has been shown to be involved in major developmental and biological processes, such as spermatogenesis, hind limb formation, hematopoiesis, and immune regulation. PLZF is localized mainly in the nucleus where it exerts its transcriptional repression function, and many post-translational modifications affect this ability and also have an impact on its cytoplasmic/nuclear dissociation. PLZF achieves its transcriptional regulation by binding to many secondary molecules to form large multi-protein complexes that bind to the regulatory elements in the promoter region of the target genes. These complexes are also capable of physically interacting with its target proteins. Recently, PLZF has become implicated in carcinogenesis as a tumor suppressor gene, since it regulates the cell cycle and apoptosis in many cell types. This review will examine the major advances in our knowledge of PLZF biological activities that augment its value as a therapeutic target, particularly in cancer and immunological diseases.